Injustice Legal System Ibuism in Indonesian Marriage Law: A Study on Polygamy for Childlessness Reasons - Yulinda, Deva; Putri, Suci Ramadhani; Elmhemıt, Hüseyin (Fakultas Syariah IAIN Madura, 2025)
This research examines the inequality of justice for women in the regulation of polygamy in Indonesia, especially Article 4 paragraph (2) letter c of the Marriage Law and Article 57 letter c of the Compilation of Islamic Law which allows husbands to practice polygamy if the wife cannot produce offspring. This research uses a qualitative approach with a normative legal analysis method. The primary data sources of this research are the Marriage Law and the Compilation of Islamic Law. The secondary data sources are Court decisions, academic literature, journals, and expert opinions relevant to this research. The data analysis technique in this research uses the content analysis method. This research argues that there has been an inequality